A comparative analysis of periodicity in the Arkansas state budget process. Issue 1 (4th March 2019) - Hoffman, Kim U.; Reese, Catherine C.
Abstract : Purpose: The purpose of this paper is to explore the impact of changes to the Arkansas budget process brought about when the people of Arkansas voted to move from a biennial to an annual budget period in 2008. The paper describes the legislative changes necessary for annual budget review and explores the impact of annual budget review on revenue forecasting, supplemental appropriations, special sessions, legislative staff workload, executive branch oversight and state spending. This research assesses legislative perceptions of annual budget review across several factors including knowledge of the state budget, ability to check the powers of the governor and overall efficacy of annual budget review. Design/methodology/approach: This exploratory research uses interview data from the Legislative Fiscal Director and data from an online survey of Arkansas state legislators. The interview and survey data were supplemented by an analysis of documents produced by legislative staff regarding supplemental appropriations, special sessions and state general revenue. Findings: The Legislative Fiscal Director interview indicates that the change in budget period had little impact on revenue forecasting, special sessions and state government spending, with the exception that supplemental appropriations for Big 6 agencies increased in a statistically significant way following the advent of the fiscal session. The legislative survey finds that the change in budget period is viewed positively by Arkansas legislators. Most legislators indicated that they prefer annual budget review to biennial budget review. Research limitations/implications: Because of the exploratory approach, the research results may lack generalizability. Originality/value: This paper surveys legislators on the efficacy of annual budget review which has seldom been done in previous research.